Analisa Korelasi Nilai QoS dan MOS Video Conference BigBlueButtonBN pada Moodle - Hayati, Nur; Nathasia, Novi Dian; Wandi, Dede; Saputra, Tri Ichsan (KITA Institut, 2021)
Virtual education is distance teaching in which teachers and students are in different places but can be connected to each other via the internet network. The virtual education system is divided into two, namely Learning Management System (LMS) and virtual classes. One of virtual education is video conferencing (vicon). A fully capable network is required to comply with Quality of Service (QoS) standards for real-time applications. This study analyzes the QoS of vicon features in LMS at the University of Nasional that is BigBlueButtonBN. Based on the QoS parameters obtained 25% throughput, 100% packet loss, 84.75% delay, 37.5% jitter and 58.5% MOS. Based on the bandwidth requirements of each parameter, the results are 61.2% or 27.9411MB. The MOS value for video 100 is 4, which results in very good images on this vicon.Keywords:BigblueButtonBN; Learning Management System; Mean Opinion Score; Quality of Service; Video Conference